Reversal of stress fibre formation by Nitric Oxide mediated RhoA inhibition leads to reduction in the height of preformed thrombi - L. Atkinson (Nature Portfolio, 2018)
Abstract Evidence has emerged to suggest that thrombi are dynamic structures with distinct areas of differing platelet activation and inhibition. We hypothesised that Nitric oxide (NO), a platelet inhibitor, can modulate the actin cytoskeleton reversing platelet spreading, and therefore reduce the capability of thrombi to withstand a high shear environment. Our data demonstrates that GSNO, DEANONOate, and a PKG-activating cGMP analogue reversed stress fibre formation and increased actin nodule formation in adherent platelets. This effect is sGC dependent and independent of ADP and thromboxanes. Stress fibre formation is a RhoA dependent process and NO induced RhoA inhibition, however, it did not phosphorylate RhoA at ser188 in spread platelets. Interestingly NO and PGI2 synergise to reverse stress fibre formation at physiologically relevant concentrations. Analysis of high shear conditions indicated that platelets activated on fibrinogen, induced stress fibre formation, which was reversed by GSNO treatment. Furthermore, preformed thrombi on collagen post perfused with GSNO had a 30% reduction in thrombus height in comparison to the control. This study demonstrates that NO can reverse key platelet functions after their initial activation and identifies a novel mechanism for controlling excessive thrombosis.